Evaluation of the protective clothing of firefighters of the Bureau of Fire Protection in Quezon City - Maristela, Candy Mae Mijares
ABSTRACT Firefighters' Personal Protective Clothing is the only protection they have during firefighting. The uniform during fire-response and operation should provide adequate protection as well as comfort and facilitation to ease in movement. Material selection, design and final evaluation test results are critical factors in predicting the protection capacity of a turnout gear. This study is an evaluation of the current condition of firefighters' protective clothing of the Bureau of Fire Protection. It identifies the different issues and concerns encountered by firefighters related to their uniform during on-ground operations. Comparison between the test results for heat transfer index, radiant heat transfer index, water resistance, breathability, thermal conductivity, and specific heat with the international standards-EN 469:2005, ASTM 518, and ASTM E1269- were observed. This descriptive exploratory research used a snowball purposive sampling in the selection of 20 firefighter respondents from ten (10) different fire sub-stations in Quezon City that were chosen by convenience sampling. The data collection included an interview method of the firefighter respondents using a 4-structured questionnaire. The study found out that there is only an average turnout gear allocation of 61.60% to 10 out of 21 fire sub-stations in Quezon City. The most common firefighter duties at the station and on-ground operation were grouped into categories namely maintenance, station maintenance, watch duties, training and wellness, on-scene communications, apparatus and equipment set-up, forcible entry and ventilation, search and rescue, and overhaul. It was also found out that the turnout gear passed the international standards for firefighters' protective clothing under the testing methods for EN 469:2005, ASTM C518, and ASTM E1269.